Ecosystem dynamics in the Liguro-Provençal Basin: the role of eddies in the biological production. - CASELLA, E.; TEPSICH, P.; COUVELARD, X.; CALDEIRA, R.M.A.; SCHROEDER, K. (Mediterranean Marine Science, 2014)
We study numerically the role of mesoscale structures in the Ligurian Sea (NW Mediterranean Sea) as a possible factor affecting the spatial distribution of the chlorophyll spring bloom. We use the Regional Ocean Modeling System (ROMS) configured for the NW Mediterranean Sea (ROMS_NWMed) and satellite derived Altimetric, Sea Surface Temperature and Chlorophyll concentration data, for years 2009 and 2010. Comparison of model output with satellite and in situ data shows agreement between numerical results and observations. There is a significant interannual variability in concentration and distribution of chlorophyll in the basin during the two years of the study. The ROMS_NWMed simulation reveals the formation of a number of mesoscale eddies along the Northern rim Current characterized by a long lifetime and closed streamlines. A significant higher number of eddies is found during the chlorophyll-rich year 2010. The high number of eddies, due to the “eddy pumping mechanism”, generate spatially and temporally localised fluxes of nutrient into the euphotic zone, thus contributing to the fertilization of the Ligurian Sea. Therefore, eddies in the Ligurian rim current can have important effects on the location of development of the main patch of chlorophyll spring bloom and consequently on the local ecosystem dynamics.